Temporal and vertical variations in phythoplankton community structure and its relation to some morphometric parameters of four Colombian reservoirs Temporal and vertical variations in phythoplankton community structure and its relation to some morphometric parameters of four Colombian reservoirs - Ramírez R. John J.; Bicudo Carlos Eduardo de Mattos; Roldán P. G.; García L. L. C. (Caldasia)
Phytoplankton samples were taken at three depths within the photie zone of eaeh of four reservoirs, Punehiná, Las Playas, El Peñol and San Lorenzo loeated in Antioquia department, Colombia. A total of 77 taxa were identified in the four reservoirs. Diatoms were not included. In all reservoirs, Chlorophyta was the dominant group. Botryococcus braunii was the dominant species at Punchiná, Las Playas and El Peñol reservoirs; Cosmarium sp. was the dominant at San Lorenzo. Temporal variation in phytoplankton showed two peaks of abundance, apparently related to precipitation. Taxonomic composition among samples from the same reservoir showed little variation. Community structure at different depths showed significant differences only at San Lorenzo reservoir. The inverse of β-diversity showed small values indicating high similarity among the reservoirs. Diversitv showed no significant assoeiation with any morphometric factor evaluated (area, retention time, altitude and age). Se efectuaron muestreos de fitoplaneton en tres profundidades de la zona fótica de los embalses Punchiná, Las Playas, El Peñol y San Lorenzo, localizados en el departamento de Antioquia, Colombia. Se identificaron un total de 77 taxones en los cuatro embalses. Las diatomeas no fueron incluídas. En todos los casos las Cholorophyta fueron el grupo dominante. Botryococcus braunii fue el taxón de mayor densidad en los embalses Punchiná, Las Playas y El Peñol; y Cosmarium sp. en el embalse San Lorenzo. La comunidad fitoplanctónica mostró dos picos de abundancia aparentemente relacionados con la precipitación. En cada embalse, la composición de taxones entre muestreos varió poco. La estructura de la comunidad a diferentes profundidades mostró diferencias significativas únicamente en el embalse San Lorenzo. El inverso de la β-diversidad presentó valores bajos que muestran la alta similaridad entre embalses. La diversidad no mostró asociación significativa con ninguno de los parámetros morfométricos evaluados (área, tiempo de retención, altitud y edad).